(untitled) (International Journal on Stereo & Immersive Media, 2021)
Este artigo apresenta uma análise das fotografias estereoscópicas de Revert Henry Klumb pertencentes à Coleção Thereza Christina Maria da Fundação Biblioteca Nacional (Coleção do Imperador). A partir de tais vistas estereoscópicas, procura-se compreender o papel que este meio visual desempenhou na configuração de um novo regime de visualidade no Brasil de oitocentos, bem como a participação da família real no processo de popularização deste medium na Corte imperial. —- This article presents an analysis of the stereoscopic photographs by Revert Henry Klumb from the Collection Thereza Christina Maria in the Brazilian National Library Foundation (Emperor´s Collection). We will explore the role played by stereoscopy in the configuration of a new visual regime in Brazil in the 1800s, as well as the contribution of the royal family in the process of popularization of this medium in the Brazilian Imperial Court.